2020
DOI: 10.1038/s41598-020-78221-5
|View full text |Cite
|
Sign up to set email alerts
|

Pupillometry pain index decreases intraoperative sufentanyl administration in cardiac surgery: a prospective randomized study

Abstract: Pupillometry has proven effective for the monitoring of intraoperative analgesia in non-cardiac surgery. We performed a prospective randomized study to evaluate the impact of an analgesia-guided pupillometry algorithm on the consumption of sufentanyl during cardiac surgery. Fifty patients were included prior to surgery. General anesthesia was standardized with propofol and target-controlled infusions of sufentanyl. The standard group consisted of sufentanyl target infusion left to the discretion of the anesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…4 It is common practice to use high doses of opioids in cardiac surgery, 7 but opioid titration using nociceptive monitoring systems has shown that the dose can be safely and significantly decreased. 12,30 The lower the dose of sufentanil, the lower may be the risk of opioid side effects. 30 Such effects may also be demonstrated by the intraoperative nonutilization of opioids during the surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 It is common practice to use high doses of opioids in cardiac surgery, 7 but opioid titration using nociceptive monitoring systems has shown that the dose can be safely and significantly decreased. 12,30 The lower the dose of sufentanil, the lower may be the risk of opioid side effects. 30 Such effects may also be demonstrated by the intraoperative nonutilization of opioids during the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients with acute renal injury (177 patients versus 178 patients, P = 1), pneumoniae (59 patients versus 42 patients, P = .104), and death (34 patients versus 34 patients, P = 1) did not differ between the 2 groups (Table 3). The balanced nonopioid general anesthesia group had shorter ICU stays (2 [1-3] days versus 3 [1][2][3][4] days, P = .001), but the overall hospital LOS did not significantly differ (8 days [7][8][9][10][11][12] versus 9 days [7][8][9][10][11][12]; P = .790).…”
Section: Secondary End Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…These made compelling arguments to apply the NOL index only until CPB initiation, providing a window of objectivity long enough to assess the block success and fine-tune opioid administration in both study arms. To date, only two other studies monitored nociception intraoperatively in cardiac surgery [ 22 , 23 ]. Interestingly, both used the pupillary pain index and reported reduced sufentanil consumption.…”
Section: Discussionmentioning
confidence: 99%
“…A PPI of 1 to 3, 4 to 6, or 7 to 9 describes numbed PDR and deep analgesia, medium PDR and suboptimal analgesia, and highly reactive PDR and uncontrolled pain, respectively. A decrease in the use of opioids was detected when this score was used as a criterion during intraoperative administration of opioids [16][17][18].…”
Section: Introductionmentioning
confidence: 99%